2008
DOI: 10.1080/15563650701638941
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen exposure in a child from hair lotion used by her mother: Clinical and hair analysis data

Abstract: Premature estrogenic effects may result from exogenous exposure to estrogenic substances. We report the case of a 36-month-old girl who presented with vaginal bleeding, uterus enlargement, and thelarche. Questioning of the parents revealed that the child's mother had used hormone-based hair lotions on her own scalp and that the child was in the habit of playing with her mother's hair while falling asleep, and that the girl played with her mother's combs and the empty lotion vials. The onset of hyperestrogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…More recent studies report endocrine disruption in women at both young and old age following inappropriate exposure to oestrogenic chemicals in personal care products - including premature breast development and menstruation in a 36-month girl following exposure to hair lotion containing oestrogenic products used by her mother [ 18 ], and, at the other extreme of age, abnormal genital bleeding and breast cancer in a 93-year old lady after long-term use of an ethynyloestradiol-containing body care cream [ 19 ]. The administration of hormone replacement therapy by skin patches relies on the ability of the hormones to be absorbed from the patch through the skin, but the effects of daily application over the long term of multiple cosmetic products containing oestrogenic chemicals warrants equal consideration [ 5 ].…”
Section: Oestrogenic Activity Of Dermally Absorbed Cosmetic Chemicalsmentioning
confidence: 99%
“…More recent studies report endocrine disruption in women at both young and old age following inappropriate exposure to oestrogenic chemicals in personal care products - including premature breast development and menstruation in a 36-month girl following exposure to hair lotion containing oestrogenic products used by her mother [ 18 ], and, at the other extreme of age, abnormal genital bleeding and breast cancer in a 93-year old lady after long-term use of an ethynyloestradiol-containing body care cream [ 19 ]. The administration of hormone replacement therapy by skin patches relies on the ability of the hormones to be absorbed from the patch through the skin, but the effects of daily application over the long term of multiple cosmetic products containing oestrogenic chemicals warrants equal consideration [ 5 ].…”
Section: Oestrogenic Activity Of Dermally Absorbed Cosmetic Chemicalsmentioning
confidence: 99%
“…Furthermore, it has been observed that long-term exposure to body care creams containing ethinyl estradiol may increase the risk of abnormal genital bleeding and breast cancer [65]. Interestingly, a case-report study found that synthetic hormones found in lotions used by the mother were present in very high concentrations in the hair of the girl [66].…”
Section: Use Of Cosmetics and Pcps And Feminine Diseasesmentioning
confidence: 99%